PEMANFAATAN SOSIAL MEDIA DALAM PEMASARAN SITU TANDON SEBAGAI DESTINASI WISATA OLAHRAGA PILIHAN MASYARAKAT KOTA TANGERANG SELATAN - Nani, Nani; Furyanah, Anah; Kurniawaty, Erlita (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT The community service activity focuses on the utilization of social media in marketing Situ Tandon as a preferred sports tourism destination for the people of South Tangerang. The main issues faced include water pollution, inadequate supporting facilities, and a lack of community awareness regarding the importance of environmental conservation. The objective of this initiative is to enhance the visibility of Situ Tandon through engaging digital marketing campaigns while educating the community about cleanliness and environmental preservation. The methods employed include socialization, waste management training, and creating appealing content on social media platforms. The expected outcomes are an increase in visitor numbers, improved water quality, and the establishment of active environmental care groups. Ultimately, this activity aims to contribute positively to local tourism development and the welfare of surrounding communities.